Wireless surveillance sytem for greenhouse crops (2014)
The agriculture in the southeast Spain has experimented important changes in the last years due to the greenhouse crops. In this kind of crops is very important the use of advanced techniques and new technologies to improve the crop efficiency. This work presents an advanced system to monitor the variables applied on greenhouse crops. The monitoring system uses a wireless sensor network (WSN) that works with 6LoWPAN and RPL as the routing protocol. It measures humidity, temperature, light, and volumetric water content in the soil. The WSN sends the recollected data to an embedded device which stores the information on a data base, so it is possible to visualize in real time the values obtained of crops as a graphic. The developed system allows installation flexibility and adaptation to any greenhouse. Because it is based on: Wireless technology, nodes can establish links automatically, and have implemented a function for saving energy which can extend the life of the batteries enough for a crop year without maintenance.